PENGELOLAAN DESA WISATA PENGELIPURAN DENGAN KONSEP GREEN ECONOMY BERBASIS MASYARAKAT LOKAL DI ERA PANDEMI COVID-19 - Putu Agus Prayogi; I Putu Bagus Suthanaya; Ni Luh Komang Julyanti Paramita Sari (Journal of Applied Management and Accounting Science, 2022)
The COVID-19 pandemic has had a huge impact on the tourism industry. The very high decrease in the number of tourist visits has caused many businesses in the tourism sector to close their businesses, including tourist villages. As one of the tourist villages in Bali, the Penglipuran Tourism Village is also affected by the COVID-19 pandemic. The management of Penglipuran Tourism Village has implemented the Green Economy concept. Where the application of the Green Economy concept can be seen from the tourism products offered are environmentally friendly products such as traditional houses that still utilize natural materials (bamboo trees), the souvenirs offered are processed products from agricultural and plantation products. The natural condition and clean and natural village environment is also a form of implementing the Green Economy concept which aims to preserve the environment. In its management, Penglipuran Tourism Village has involved the community starting from the planning, implementation and evaluation stages. It can be seen that pokdarwisa as a management institution is an institution established by the traditional village and the department where its members come from